Genome-wide identification, characterization, evolution and expression analysis of the DIR gene family in potato (Solanum tuberosum) - Jia, Wenqi; Xiong, Yuting; Li, Man; Zhang, Shengli; Han, Zhongcai; Li, Kuihua (Frontiers in Genetics, 2023)
The dirigent (DIR) gene is a key player in environmental stress response and has been identified in many multidimensional tube plant species. However, there are few studies on the StDIR gene in potato. In this study, we used genome-wide identification to identify 31 StDIR genes in potato. Among the 12 potato chromosomes, the StDIR gene was distributed on 11 chromosomes, among which the third chromosome did not have a family member, while the tenth chromosome had the most members with 11 members. 22 of the 31 StDIRs had a classical DIR gene structure, with one exon and no intron. The conserved DIR domain accounts for most of the proteins in the 27 StDIRs. The structure of the StDIR gene was analyzed and ten different motifs were detected. The StDIR gene was divided into three groups according to its phylogenetic relationship, and 22 duplicate genes were identified. In addition, four kinds of cis-acting elements were detected in all 31 StDIR promoter regions, most of which were associated with biotic and abiotic stress. The results showed that the StDIR gene had a certain response to cold stress, salt stress, ABA and drought stress.This study provides new candidate genes for improving potato's resistance to stress.Keywor ds: Abiotic stress; Bioinformatics; DIR; Gene family; Potato 1. Intr oduction Potato (Solanum tuberosum) is an important non-cereal food crop with a global planting area of about 19.3 million hm2 and an annual output of nearly 400 million t, second only to rice, wheat and maize [1,2]. In recent years, people's demand for potato is increasing day by day, and the demand for planting areas is also gradually increasing, but the resulting planting problems are also increasing significantly. These consequent problems caused a large reduction in potato production, resulting in great economic losses. In order to cope with severe biotic and abiotic stress, plants also spontaneously evolved a series of defense measures to quickly respond to the complex environment, so as to reduce the damage and strive for more survival resources [3,4]. Plants respond to complex environments by activating many different genes, including the DIR protein [5][6][7].